Pig - Sarnoski, Michael; Block, Vanessa; Sarnoski, Michael; Cage, Nicolas, 1965-; Wolff, Alex, 1997-; Arkin, Adam; Belforte, Nina; Neon (Firm); Aywon Film Corp.; Endeavor Content (Firm); Pulse Films; Blockbox Entertainment (Firm); et al. ([United States] : Decal, 2021)
A truffle hunter who lives alone in the Oregonian wilderness must return to his past in Portland in search of his beloved foraging pig after she is kidnapped.
Title from web page.
Originally released as a motion picture in 2021.
Wide screen.
New DVD 2023 Spring.
Nicolas Cage, Alex Wolff, Adam Arkin, Nina Belforte, Dalene Young, Gretchen Corbett, Darius Pierce.
Rating: R; for language and some violence.
Keywords: Swine -- Drama; Hermits -- Drama; Pet loss -- Drama; Truffle culture -- Drama; Hermits; Pet loss; Swine; Truffle culture; Drama; Video recordings for the hearing impaired; Feature films